New aspects of sulfur biogeochemistry during ore deposition from δ34S of elemental sulfur and organic sulfur from the Here's Your Chance Pb/Zn/Ag deposit - Holman, Alex; Grice, Kliti; Greenwood, Paul; Böttcher, M.; Walshe, J.; Evans, Katy (Elsevier Science BV, 2014)
Sulfur isotope studies of base metal sulfide deposits have mostly focussed on sulfide minerals, but elemental sulfur and organic sulfur are also potentially significant components of the sulfur cycle during ore deposition. The δ34S of elemental sulfur and organic sulfur isolated from the Paleoproterozoic Here's Your Chance (HYC) Pb/Zn/Ag deposit (McArthur Basin, northern Australia) were measured to be between + 5 and + 8‰, approximately 6 to 7‰ heavier than the median values of first-generation HYC sulfides. Elemental sulfur and organic sulfur are thought to have been formed contemporaneously with the first generation of metal sulfides. The δ34S of organic sulfur showed an increasing trend along the path of the mineralising fluid, as sulfate was progressively 34S-enriched due to Rayleigh distillation. The δ34S data support a model in which bacterial sulfate reduction produced dissolved sulfide with δ34S of 0 to + 5‰. The subsequent oxidation of sulfide produced reactive sulfur species such as polysulfide ions, which were then incorporated into organic matter.